The Interface of Competition Law, Industrial Policy and Development Concerns The Case of South Africa - Strunz, Balthasar (Munich Studies on Innovation and Competition,, 2018)
This book analyses essential concepts of competition law and industrial policy, and shows where the two areas clash with and complement each other, respectively. The discussion takes place in the context of developing countries, taking into consideration their realities and specific needs. South Africa serves as a real-world example for competition law that goes beyond the notion of consumer welfare. An in-depth analysis of the enforcement of South African law illustrates how the law is used both to combat the negative effects of past industrial policy, and to accommodate current economic and social needs. The book is intended for all readers with an interest in the enforcement of competition law in developing countries. It will particularly benefit those who want to learn about unorthodox approaches that integrate the concept of "public interest" and social imperatives into the application of competition law.